2020
DOI: 10.1007/s40194-020-00978-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-assisted cracking in GMA welding of high-strength structural steels using the modified spray arc process

Abstract: High-strength structural steels are used in machine, steel, and crane construction with yield strength up to 960 MPa. However, welding of these steels requires profound knowledge of three factors in terms of avoidance of hydrogen-assisted cracking (HAC): the interaction of microstructure, local stress/strain, and local hydrogen concentration. In addition to the three main factors, the used arc process is also important for the performance of the welded joint. In the past, the conventional transitional arc proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“… Cold-cracking Cold cracking occurs due to high hardness and/or low toughness of the material [ 24 ]. This can be intensified due to external restraints or other phenomena like the hydrogen assisted cracking [ 25 , 26 ]. Stress relief cracking Cracking which occurs due to high strength and low ductility during post weld heat treatment [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Cold-cracking Cold cracking occurs due to high hardness and/or low toughness of the material [ 24 ]. This can be intensified due to external restraints or other phenomena like the hydrogen assisted cracking [ 25 , 26 ]. Stress relief cracking Cracking which occurs due to high strength and low ductility during post weld heat treatment [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cold cracking occurs due to high hardness and/or low toughness of the material [ 24 ]. This can be intensified due to external restraints or other phenomena like the hydrogen assisted cracking [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations carried out using the Mod. SA in the implant test showed that the deeper weld penetration profile and the increased welding current result in higher diffusible hydrogen concentrations and longer time-to-failure of the specimens until fracture [39]. However, the critical implant stress for crack initiation was not affected.…”
Section: Introductionmentioning
confidence: 94%
“…For the investigations, the quenched and tempered high-strength structural steel S960QL (BM) according to EN 10025-6 [44] with a plate thickness of 20 mm was chosen. This steel is typically used in mobile crane construction and shows high susceptibility to HAC in GMAW [37,39]. The welds were carried out with micro-alloyed filler materials of the same type.…”
Section: Test Materialsmentioning
confidence: 99%
“…They provide superior strength per weight than conventional structural steels and yield cost savings by simplifying or eliminating heat treatment processes [3][4][5][6]. Hydrogen embrittlement was investigated due to the offshore application of these steels [7][8][9]. The effect of welding on the mechanical properties of these steels has been studied with conventional uniaxial tensile testing, the Charpy V-notch impact test, and a hardness test [3,6,10,11], and optimum welding parameters for gas metal arc welding have been proposed [11].…”
Section: Introductionmentioning
confidence: 99%